A first insight into the scanning behaviour of the presocial blow fly larvae. (22nd September 2015) - Boulay, Julien; Betremieux, Cécile; Hédouin, Valéry; Charabidzé, Damien
Abstract: Aggregation of necrophagous larvae has several benefits: the sharing of salivary enzymes (exodigestion), temperature regulation, protection from predators and parasites, etc., and is well developed in blow flies (Diptera: Calliphoridae). The present study focuses on the aggregation mechanism used by the necrophagous larvae of Lucilia sericata Meigen, the common green bottle fly. The ability of single larva to detect and follow a signal (trail) created by conspecifics is investigated initially. A circular ring is drawn in a Petri dish where 20 starved larvae have crawled for a period of 30 min. A naïve (test) larva is then placed in the dish and video‐tracked. Naïve larvae are able to detect the boundaries of the larvae‐crawled area and stay preferentially within this conspecific‐marked zone. In a second step, the orientation of larvae by scanning, a dedicated, ground‐signal detection behaviour of dipteran larvae, is analyzed. Four experimental conditions are tested: control, presence of food, conspecifics, and food + conspecifics. When conspecifics have been previously present in a given area, the scanning behaviour by naïve larvae in this area decreases (both in number and frequency of scans). Accordingly, scanning by necrophagous larvae of L. sericata should be considered not only as locomotion behaviour, but also as a potential way to detect signals from conspecifics for the purpose of aggregation. The chemical composition of the attractant(s), the behavioural effects (attraction or retention) and the implication of larval signalling in the aggregation process are new fields to explore.